Screening, Purification, and Characterization of Cellulase from Fungi Isolated from Used Mushroom Substrate - IWAN SASKIAWAN; NUR HASANAH (Indonesian Society for microbiology, 2015)
Alarge number of microorganism especially filamentous fungi has ability to degrade cellulose. The purpose of this study was to conduct screening, purification, and characterization of cellulase from fungi which was isolated from used paddy straw mushroom substrate. Screening of cellulytic activity using CMC medium shown that 11 out of 20 isolates of fungi produced a clearing zone surrounding fungal colony. Among them isolate number JMF 12 showed the highest cellulase activity and was further used for purification and characterization. The cellulase was purified to electrophoretical homogeneity by ammonium sulfate precipitation, dialyzed by Novagen D-Maxi TubeTM Dialyzer, and Sephadex G-100 gel filtration chromatography. The recovery and purification fold was 3.82 % and 1.98 respectively, after Sephadex G-100 gel filtration chromatograph. The o purified cellulase had an optimal pH and temperature at 6 and 45 C.Â The Km and Vmax of cellulase was 11.43 mM and 0.006mmol/min respectively. The purified cellulase was activated by Na+ and Zn++ but inhibited by Ca++, Co++, Fe++, andÂ Hg++ .